2008
DOI: 10.1086/523306
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Demographic Decline: A Potential Effect Mediated by Impairment of Reproduction and Immune Function in Cyclic Vole Populations

Abstract: The stress response is initially adaptive, operating to maintain homeostasis. However, chronic long-term exposure to stressors may have detrimental effects. We proposed that chronic stress may be a major factor in demographic vole cycles, inducing decline in high-density populations. We monitored four populations of the fossorial water vole Arvicola scherman, which undergo pluriannual demographic cycles in the Jura Mountains (France). Sampling was conducted during the high densities and the decline. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 54 publications
1
68
0
Order By: Relevance
“…1995). Spatio‐temporal variations in vole abundances have been described in a previous study for these localities (Charbonnel et al. 2008a).…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…1995). Spatio‐temporal variations in vole abundances have been described in a previous study for these localities (Charbonnel et al. 2008a).…”
Section: Methodsmentioning
confidence: 54%
“…One person carried out all injections and thickness measurements. Part of these data has previously been published (Charbonnel et al. 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…Boonstra et al (1998a) also found that hares in winter were more stressed during the decline phase when predator numbers were greatest than during the late low phase when they were the lowest. Charbonnel et al (2008) also found that cyclic populations of water voles, Arvicola scherman, were more stressed during the decline phase compared with the peak. Additionally, an increase in the number of predators has been shown to increase glucocorticoid (GC) levels in a number of other non-cyclic freeranging mammals and birds (Silverin 1997;Hik et al 2001;Scheuerlein et al 2001).…”
Section: Fecal Cortisol Metabolitesmentioning
confidence: 84%
“…Glucocorticoids (cortisol and corticosterone) are released under stressful conditions to help the organism defend itself against a perceived stressor [22]. Although the short term release of these hormones is known to increase fitness via energy mobilization, prolonged periods of high glucocorticoid concentrations are known to decrease fitness by affecting reproductive success, immuno-suppression, growth, and muscular atrophy [23–26]. Long-term anthropogenic disturbance has been shown to increase glucocorticoid levels in many wildlife taxa, e.g.…”
Section: Introductionmentioning
confidence: 99%